Polymetallic Metallogenic System - Yang, Liqiang (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Within the last decade, the high and continuing demand for precious and base metals, as well as critical elements, has prompted a global rush on a scale never before seen. This eventually resulted in the demand for considerable innovation and improvement in mineral deposit genetic modelling and ore formation regimes for the many different types of gold deposits, now recognized, and paralleled by the wide employment of exploration techniques and a rapid expansion of geological databases. This Special Issue will show case studies of porphyry polymetal systems, orogenic gold formations, water–rock reaction, ore-forming structure evolution, mineralogy and petrology of ore deposit, ore formation regime, geochronology and geochemistry of ore deposit, ore-forming evolution, mineral exploration and cutting-edge technology in ore deposit study.